HMG-CoA Reductase Inhibitors Decrease CD11b Expression and CD11b-Dependent Adhesion of Monocytes to Endothelium and Reduce Increased Adhesiveness of Monocytes Isolated From Patients With Hypercholesterolemia - Weber, Christian; Erl, Wolfgang; Weber, Kim S.C; Weber, Peter C (Journal of the American College of Cardiology, 1997)
Objectives. This study sought to determine whether inhibitors of 3-hydroxy-3-methyl-glutaryl coenzyme A (HMG-CoA) reductase affect CD11b expression and adhesiveness of monocytes in vitro and after treatment of patients with hypercholesterolemia. Background. HMG-CoA reductase inhibitors improve survival of patients with coronary heart disease (CHD) and prevent CHD in hypercholesterolemic men. Because these drugs have been shown to modulate monocyte functions, they may act by reducing monocyte adhesion to endothelium, which is crucial in atherogenesis. Methods. Isolated human blood monocytes were subjected to flow cytometric detection of CD11b and adhesion assays on fixed human endothelial cells after treatment with lovastatin in vitro or ex vivo before and after treatment of hypercholesterolemic patients with HMG-CoA reductase inhibitors. Results. The integrin heterodimer CD11b/CD18 expressed on monocytes interacts with intercellular adhesion molecule-1 on endothelium and is involved in monocyte adhesion to endothelium. Treatment of monocytes with lovastatin in vitro slightly and dose dependently reduced surface expression of CD11b on monocytes. Moreover, lovastatin inhibited CD11b-dependent adhesiveness to fixed endothelium of unstimulated monocytes or monocytes stimulated with monocyte chemotactic protein 1. Coincubation with mevalonate, but not with low density lipoprotein (LDL), reversed the effects of lovastatin, suggesting that early cholesterol precursors, but not cholesterol, are crucial for adhesiveness of CD11b. In hypercholesterolemic patients, adhesion of isolated monocytes to endothelium ex vivo was dramatically increased over values in healthy control subjects. Treatment of these patients with the HMG-CoA reductase inhibitors lovastatin or simvastatin (20 to 40 mg/day) for 6 weeks slightly decreased total and LDL cholesterol plasma levels and monocyte CD11b surface expression but resulted in a significant reduction of monocyte adhesion to endothelium (p < 0.01, n = 7). Conclusions. The reduction of CD11b expression and inhibition of CD11b-dependent monocyte adhesion to endothelium may crucially contribute to the clinical benefit of HMG-CoA reductase inhibitors in CHD, independent of cholesterol-lowering effects.